2022
DOI: 10.1177/17588359221122725
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validity and clinical utility of Ki67 in early breast cancer

Abstract: Ki67 represents an immunohistochemical nuclear localized marker that is widely used in surgical pathology. Nuclear immunoreactivity for Ki67 indicates that cells are cycling and are in G1- to S-phase. The percentage of Ki67-positive tumor cells (Ki67 index) therefore provides an estimate of the growth fraction in tumor specimens. In breast cancer (BC), tumor cell proliferation rate is one of the most relevant prognostic markers and Ki67 is consequently helpful in prognostication similar to histological grading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
(117 reference statements)
0
12
0
1
Order By: Relevance
“…These results suggested that the GP‐20@Gla group grew fastest because Ki67 is the most crucial protein marker of cell proliferation. [ 30 ] This study's results of CD31 and Ki67 IF staining assay were interactive. A higher degree of vascularization is conducive to transporting oxygen and nutrients, which improves the speed and quality of tissue regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the GP‐20@Gla group grew fastest because Ki67 is the most crucial protein marker of cell proliferation. [ 30 ] This study's results of CD31 and Ki67 IF staining assay were interactive. A higher degree of vascularization is conducive to transporting oxygen and nutrients, which improves the speed and quality of tissue regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have discovered that Ki67 can be used as a diagnostic and prognostic biomarker in renal cancer ( 6 ), breast cancer ( 20 , 22 ), ovarian cancer ( 23 ), craniopharyngioma ( 24 ) and neuroendocrine neoplasms ( 25 ). However, the prognostic role of Ki67 in prostate cancer remains ambiguous and has not been thoroughly explored.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most studies have been conducted on the predictive and clinical effectiveness of Ki67, but few studies have utilized the characteristics of Ki67 and the ADC in combination. We strongly believe in the importance of ADCs in PCa and hold the opinion that Ki67 can be applied in combination with postoperative PSA testing and imaging parameters (i.e., the ADC) to improve specificity and sensitivity ( 9 , 20 , 21 ). The aim of this study was to determine whether Ki67 had any predictive value for prostate cancer patients who received surgery and endocrine therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the manual quantification of Ki-67 + tumor cells is time consuming and cumbersome, the computerized quantification of Ki-67 + cancer cells has been extensively studied [9,15,16]. Despite such efforts, automated differentiation between normal healthy prostate tissue and prostate cancer still represents the most significant hurdle in its routine use, which is why the cumbersome assessment of Ki-67 LI, also known from breast cancer, in at least 200-500 tumor cells is currently not done in routine clinical practice [17,18].…”
Section: Introductionmentioning
confidence: 99%